Equity Weighting and the Marginal Damage Costs of Climate Change - David Anthoff; Cameron Hepburn; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2007)
Climate change would impact different countries differently, and different countries have different levels of development. Equity-weighted estimates of the (marginal) impact of greenhouse gas emissions reflect these differences. Equity-weighted estimates of the marginal damage cost of carbon dioxide emissions are substantially higher than estimates without equity-weights; equity-weights may also change the sign of the social cost estimates. Equity weights need to be normalised. Our estimates differ by two orders of magnitude depending on the region of normalisation. A discounting error of equity weighted social cost of carbon estimates in earlier work (Tol, Energy Journal, 1999), led to an error of a factor two. Equity-weighted estimates are sensitive to the resolution of the impact estimates. Depending on the assumed intra-regional income distribution, estimates may be more than twice as high if national rather than regional impacts are aggregated. The assumed scenario is important too, not only because different scenarios have different emissions and hence warming, but also because different scenarios have different income differences, different growth rates, and different vulnerabilities. Because of this, variations in the assumed inequity aversion have little effect on the marginal damage cost in some scenarios, and a large effect in other scenarios.
Keywords: Q54; 330; Marginal Damage Costs; Climate Change; Equity; Klimaveränderung; Volkswirtschaftlicher Schaden; Gerechtigkeit; Welt